Dynamic Volume Perfusion Computed Tomography Parameters versus RECIST for the Prediction of Outcome in Lung Cancer Patients Treated with Conventional Chemotherapy. Issue 1 (January 2015) - Sudarski, Sonja; Shi, Jingyun; Schmid-Bindert, Gerald; Manegold, Christian; Pilz, Lothar R.; Zhou, Caicun; Schoenberg, Stefan O.; Henzler, Thomas
<x xml:space="preserve">Abstract</x> Introduction: To compare dynamic volume perfusion computed tomography (dVPCT) parameters with Response Evaluation Criteria in Solid Tumors (RECIST 1.1) for prediction of therapy response and overall survival (OS) in non–small-cell lung cancer (NSCLC) and small-cell lung cancer (SCLC) patients treated with conventional chemotherapy. Methods: A total of 173 lung cancer patients (131 men; 61 ± 10 years) undergoing dVPCT before (T1) and after chemotherapy (T2) and follow-up were prospectively included. dVPCT-derived blood flow, blood volume, mean transit time, and permeability (PERM) were assessed, compared between NSCLC and SCLC and patients' response to therapy was determined according to RECIST 1.1. Results: One hundred of one hundred and seventy-three patients underwent dVPCT at T1 and T2 within a median of 44 (range, 31–108) days. dVPCT values were differing in NSCLC and SCLC, but were not significantly differing between patients with partial response, stable, or progressive disease. Eighty-five patients (NSCLC = 72 and SCLC = 13) with a follow-up for greater than or equal to 6 months were analyzed for OS. Fifty-six of eighty-five patients died during follow-up. Receiver operating characteristic analysis determined T1/T2 with highest predictive values regarding OS for blood flow, blood volume, mean transit time, and permeability (area under the curve: 0.53, 0.61, 0.54, and 0.53, respectively, all p > 0.05). Kaplan–Meier statistics revealed OS of patient groups assigned according to dVPCT T1/T2 cutoff values was not differing for neither dVPCT parameter, whereas RECIST groups significantly differed in OS (p = 0.02). Cox proportional hazards regression determined progressive disease status to independently predict OS (p = 0.004), while none of the dVPCT parameters did so. Conclusions: dVPCT values, differ between NSCLC and SCLC, are not related to RECIST 1.1 classification and do not improve OS prediction in lung cancer patients treated with conventional chemotherapy.